Analisis Gaya Kepemimpinan dalam Keberlangsungan Bisnis Pada Masa Pandemi Covid-19 : Studi Pada CV. Kartika Sari - Ainaya Alfatiha, Raja; Hermanto, Bambang; Wulan Tresna, Pratami; Husna, Asmaul (Bahtera Inovasi, 2022)
Business continuity is the main goal for business actors in running their business, but during the Covid-19 pandemic there are many challenges to achieve business continuity. So business leaders need to determine the right strategy so that business processes can continue. In this case the leadership style will greatly affect the direction of the company's motion, so as to create business continuity, leaders who are able to understand goals are needed. So the purpose of this research is to analyze the transformational leadership style in achieving business continuity in one of the Small and Medium Industries (IKM) in Tanjung Pinang City, namely Citra Sari Snack and Catering. The method used in this study is qualitative using semi-structured interview techniques to obtain accurate information and also primary data from the object of research. The result of this research is that the owner of Citra Sari uses a transformational leadership style and to achieve business continuity is done by setting goals, updating strategies, creating innovations, and taking risks.